2021
DOI: 10.1111/xen.12720
|View full text |Cite
|
Sign up to set email alerts
|

MRI monitoring of transplanted neonatal porcine islets labeled with polyvinylpyrrolidone‐coated superparamagnetic iron oxide nanoparticles in a mouse model

Abstract: Islet transplantation is a potential treatment option for certain patients with type 1 diabetes; however, it still faces barriers to widespread use, including the lack of tools to monitor islet grafts post‐transplantation. This study investigates whether labeling neonatal porcine islets (NPI) with polyvinylpyrrolidone‐coated superparamagnetic iron oxide nanoparticles (PVP‐SPIO) affects their function, and whether this nanoparticle can be utilized to monitor NPI xenografts with magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“… 58 , 59 , 60 In general, the number of islets required to improve blood glucose levels in mouse diabetes models is species dependent. In the case of subrenal capsule transplantation into immunocompromised mice, which is often used in experiments due to its relatively high viability, it has been reported that 100–200 islets are required for mouse islets 61 , 62 , 63 and 500–2,000 islets for human islets, 63 , 64 , 65 , 66 while porcine islets require significantly more islets, about 2,000–12,600 IEQ) 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Discussionmentioning
confidence: 99%
“… 58 , 59 , 60 In general, the number of islets required to improve blood glucose levels in mouse diabetes models is species dependent. In the case of subrenal capsule transplantation into immunocompromised mice, which is often used in experiments due to its relatively high viability, it has been reported that 100–200 islets are required for mouse islets 61 , 62 , 63 and 500–2,000 islets for human islets, 63 , 64 , 65 , 66 while porcine islets require significantly more islets, about 2,000–12,600 IEQ) 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Discussionmentioning
confidence: 99%